Collaborative modification strategy to improve the formation of biochar-derived persistent free radicals for aniline removal via peroxymonosulfate activation - Zilong Zhao; Shuting Zhu; Shuyu Qi; Ting Zhou; Yang Yang; Feng Wang; Qi Han; Wenyi Dong; Hongjie Wang; Feiyun Sun (Biochar)
Abstract This study explores a novel approach to biochar modification aimed at increasing persistent free radical (PFR) formation on biochar surfaces, thereby enhancing aniline removal via peroxymonosulfate (PMS) activation. By adjusting pyrolysis temperatures and doping ratios, optimal conditions were established. Spearman's analysis highlighted the importance of C=C bonds, the ID/IG ratio, and pyridinic N in generating PFRs. The modified biochar derived at 500 ℃ (MB500), in conjunction with the PMS system demonstrated impressive efficiency, achieving 92% aniline removal within 30 min. Detailed adsorption tests and active species detection indicated that aniline degradation occurred through both direct oxidation by PFRs and indirect oxidation by reactive species, particularly superoxide radicals (O₂⋅⁻). Furthermore, the synergistic effects of heteroatom nitrogen and Na2CO3 modifications significantly impacted PFR formation and stability. These findings provide valuable insights into the mechanisms of PFR-mediated catalytic oxidation, highlighting the key roles of pyridinic rings, with or without oxygenated groups, in enhancing catalytic performance of biochar. This research advances the understanding of biochar surface chemistry and presents an effective strategy for developing high-performance biochar-based catalysts for environmental remediation, addressing the limitations of unmodified biochar through targeted surface modifications. Graphical Abstract